2015 Unmanned aerial system (UAS)-derived orthoimage mosaics and digital terrain models of the SE lava flow margin, Holuhraun lava flow-field, Vatnajökull National Park, Iceland - Scheidt, Stephen P.; Hamilton, Christopher W. (University of Arizona Research Data Repository, 2021)
Using a Phantom 3 Pro imaging system, aerial images were acquired over a short section of the SE Holuhraun lava flow margin, adjacent interior and adjacent river systems. Images were initially geocoded using the device's onboard GPS and a ground control points (GCPs) network. Final products were coregistered to more precise geocoded image data collected later in 2016. Images were processed into geodetically-controlled digital terrain models (DTMs) and orthomosaics using the commercial software package Pix4Dmapper Pro version 2.0.81. In Pix4Dmapper Pro, data products were geocoded by attributing the 3D coordinates of geocoded image coregistration targets to corresponding pixels in a subset of 2D images. The 2016 image data used for coregistration utilized DGPS measurements. To estimate the localization accuracy, we used a network of N = 7 coregistration points; the resulting mean of the root mean square error (RMSE) of x, y, and z directions (i.e., latitude, longitude, and elevation) is 10.6 cm. Both the DTM and orthomosaic products have a spatial resolution of 2 cm/pixel, but the DTM has an effective resolution of ~4 cm/pixel. Topic Categories (ISO 19115) elevation, geoscientificinformation, imageryBaseMapsEarthCover Feature and Attribute Definitions A georeferenced raster displaying elevation data generated from digital camera image data using multi-view stereophotogrammetry methods. Date of Content 2015-08-24 For inquiries regarding the contents of this dataset, please contact the Corresponding Author listed in the README.txt file. Administrative inquiries (e.g., removal requests, trouble downloading, etc.) can be directed to data-management@arizona.edu This item is part of Unmanned aerial system (UAS)-derived orthoimage mosaics and digital terrain models of the northeastern portion of the Holuhraun lava flow-field, Iceland